If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2e + -12 = 7e + 8 Reorder the terms: -12 + 2e = 7e + 8 Reorder the terms: -12 + 2e = 8 + 7e Solving -12 + 2e = 8 + 7e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-7e' to each side of the equation. -12 + 2e + -7e = 8 + 7e + -7e Combine like terms: 2e + -7e = -5e -12 + -5e = 8 + 7e + -7e Combine like terms: 7e + -7e = 0 -12 + -5e = 8 + 0 -12 + -5e = 8 Add '12' to each side of the equation. -12 + 12 + -5e = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -5e = 8 + 12 -5e = 8 + 12 Combine like terms: 8 + 12 = 20 -5e = 20 Divide each side by '-5'. e = -4 Simplifying e = -4
| 2x+18=3x+12 | | 4x+3x-3=20 | | 5d-12=23 | | 0.1=3x+78 | | 15+4c=27 | | 6(g-2)+g=6(g-4) | | 5c-7=41 | | 8-8x-4=-17+4x-15 | | (4x+1)=(5x-15) | | 9m+11=38 | | -3=x/5+5 | | 2x-10=-3(x-5) | | .21428571a+.95238095=.57142857 | | 7-(3y-9)=1-4y | | 3x+15=3+5x-8 | | -1x-3=x+4 | | -3x-12=9x+12 | | 28=2d | | -5x+30-7x=3x+120 | | 4x^2-39x+81= | | 3x-2y=33 | | 2x+5x+10=-60 | | 8r^2-10r+3=0 | | 4p*5q=60y | | x*0.10+0.35=10 | | -2K+10=-12 | | 6x-4=-3x+5 | | 13y-3=53-y | | 4p+5q=60y | | a/6=-9 | | 5x^2-24x=-28 | | 7x+14=9x+2 |